PRODUKTIVITAS KOMBINASI PEMAKAIAN ALAT BERAT EXCAVATOR DAN DUMP TRUCK PADA PEKERJAAN GALIAN PROYEK PEMBANGUNAN GUDANG CJ LOGISTIC SAFE’N’LOCK ECO INDUSTRIAL PARK - Pramesti, Reinanda Aurellia (Jurnal Vokasi Teknik Sipil, 2025)
In the CJ Logistic Safe’n’Lock Eco Industrial Park Warehouse construction project, there is excavation work that requires heavy equipment such as excavators and dump trucks as aids for earthmoving work. Although this project has been running, the arrangement of heavy equipment used has not been optimal, based on observations made during the earthmoving period there is a waiting time for the excavator to the dump truck, this can affect productivity and also reduce the efficiency of the work process. This study aims to analyze the productivity of excavators and dump trucks, compare combinations of heavy equipment to determine the most optimal choice in terms of time and cost, and determine the number of tools and the most efficient work duration. With a quantitative approach and comparative analysis used to evaluate two alternative combinations of heavy equipment. The calculation results show that the productivity of the Hitachi zx210f-5g excavator is 47.62 m3/hour, and for the productivity of the Mitsubisi Fuso FM 517 HS 7.5 MT dump truck is 26.32 m3/hour. The results of the analysis indicate that combination 3 is the most optimal combination. This combination provides a duration acceleration of 65.71% or 23 hours faster compared to the initial condition, with a cost increase of Rp11,884,875.00 or 39.33%.